Eosinophilic colitis in children - Grzybowska-Chlebowczyk, Urszula; Horowska-Ziaja, Sabina; Kajor, Maciej; Więcek, Sabina; Chlebowczyk, Wojciech; Woś, Halina (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction: Eosinophilic colitis, which is a rare form of eosinophilic gastrointestinal diseases, occurs as primary and secondary allergic eosinophilic colitis of the gastrointestinal tract infection, inflammatory bowel disease, celiac disease, and vasculitis. The diagnosis is based on a significant amount of eosinophils in the inflammatory infiltrate of the colon wall. Aim: To analyze the clinical picture taking into account comorbidities and endoscopic picture in children with eosinophilic colitis. Material and methods : The test group consisted of 43 children, the average age – 12.1 years diagnosed with eosinophilic colitis (according to the Whitington scale) hospitalized in the Gastroenterology Unit, Department of Pediatrics of the Medical University of Silesia in Katowice. Testing for food allergies, celiac disease, inflammatory bowel disease, gastrointestinal diseases and parasitic diseases was performed in the group of children and the analysis concerned the intensity of eosinophilic infiltration of the colon mucosa with the severity of clinical symptoms, endoscopic picture, the presence of inflammatory bowel disease, and food allergy. Results: Half of the tested children suffered from isolated eosinophilic colitis but the rest of them had eosinophilic infiltrate with inflammatory bowel disease more often, however, the Crohn’s disease. The endoscopic image was uncharacteristic, and grade III in the Whitington scale was predominant in the histopathological examination, in most cases located in the entire large intestine. The higher level of total IgE was found in less than half of the patients and it did not correlate with the severity of eosinophilic infiltration. It was shown that the severity of eosinophilic infiltration correlated with exacerbation of clinical symptoms, endoscopic image, and the presence of inflammatory bowel disease. The higher level of antibodies of ASCA and ANCA was found in approximately 20% of the children with isolated eosinophilic colitis and 63% of children with Crohn’s disease. Conclusions : The higher concentration of total IgE in less than half of the patients with eosinophilic colitis indicates the need for improving allergy diagnosis also in terms of IgE-independent allergy. The presence of higher levels of antibodies of ASCA and ANCA in some of the patients with isolated eosinophilic colitis indicates the need for further observation for the occurrence of inflammatory bowel disease.